Evaluation of the Masking Effect of Different Glass Ionomer Restorations following Silver Diamine fluoride and Potassium Iodide Application: An In Vitro Study - Raafat, Rasha; Abuzaid, Mohamed; Abd ElAziz, Rawda Hesham (European Journal of General Dentistry, 2022)
Objectives This is an in vitro study that aimed to evaluate the ability of different glass ionomer restorations to mask the discoloration produced following silver diamine fluoride (SDF) only and after potassium iodide (KI) application.Materials and Methods Thirty-six extracted human adult posterior teeth were collected. Box-shaped cavities (4 × 2 × 2 mm3) were prepared along the cementoenamel junction. Specimens were randomly divided into two major groups according to the materials applied under the restorations group (A) 38% silver diamine fluoride (SDF) followed by immediate application of potassium iodide (KI), group (B) 38% silver diamine fluoride (SDF) only. Each group was further subdivided according to the restorative material applied as follows (n = 6): subgroup (I) zirconia reinforced glass ionomer, subgroup (II) resin-modified glass ionomer restoration, and subgroup (III) high viscous glass ionomer restoration. Color assessment of all specimens was performed using a reflective spectrophotometer. Specimens' color was assessed color of normal dentin then assessed immediately after application of SDF (group A) and after application SDF + KI (group B) with the respective restorative material used.Statistical Analysis Data showed parametric distribution and variance homogeneity and were analyzed using one-way analysis of variance followed by Tukey's post hoc test.Results Intergroup comparisons showed that for SDF and SDF + KI samples, there was a significant difference between the different restorative materials (p < 0.001). For glass ionomer, SDF samples had significantly higher color change value than SDF + KI (p < 0.001), while for RMGI and zirconia reinforced glass ionomer, SDF + KI samples had significantly higher value (p < 0.001) although zirconia reinforced glass ionomer showed the least color change following SDF (6.00 ± 2.74).Conclusion Within the limitations of this study, we could conclude that using zirconia reinforced glass ionomer could have a good masking effect on discoloration produced by SDF. While the resin-modified glass ionomer restoration showed more discoloration and darkening effect even after using of KI. Also, using KI in combination with SDF had a good masking effect on discoloration that produced by SDF.
Keywords: laboratory research; potassium iodide; silver diamine fluoride; resin-modified glass ionomer; zirconia reinforced glass ionomer